(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
The digital divide between men and women is complete prejudice against women, and can result an undesirable hurdle to their involvement in globally. It is also a hindrance on the progress of the global economy. As a result of decreasing price of connectivity and hardware, skills shortages have topped obstacles of access as the primary contributor to the gender digital divide. This paper presents a brief study of issues raised due to digital divide and its impact on women of society.